2007
DOI: 10.1038/sj.ki.5002036
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein induces endothelin-mediated kidney injury through enhanced intrinsic acid production

Abstract: Dietary protein as casein (CAS) augments intrinsic acid production, induces endothelin-mediated kidney acidification, and promotes kidney injury. We tested the hypothesis that dietary CAS induces endothelin-mediated kidney injury through augmented intrinsic acid production. Munich-Wistar rats ate minimum electrolyte diets from age 8 to 96 weeks with 50 or 20% protein as either acid-inducing CAS or non-acid-inducing SOY. Urine net acid excretion and distal nephron net HCO3 reabsorption by in vivo microperfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
80
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 29 publications
5
80
1
Order By: Relevance
“…Consistent with this hypothesis, increased proximal tubule proton secretory capacity has been reported in response to metabolic acidosis and was shown to be mediated, at least in part, by increased activation of 18). Micropuncture studies in rat distal tubule have found that net acidification is also stimulated in these segments after a dietary acid load and that the increments are mediated in part by increased bosentan-inhibitable ET activity as modulated both by ET-induced apical Na/H exchange and by 33).While the authors did demonstrate higher plasma aldosterone levels in NaCl-restricted rats with higher acid loads from a high protein diet and that bosentan reduced the hyperaldosteronism, the micropuncture studies, including those showing an effect of sprironolactone, were performed with perfusate containing high concentrations of sodium (10). Since mineralocorticoid excess has no effect on renal or systemic acid-base equilibrium in NaCl-restricted acidotic dogs with high acid loads (9), it is unclear how the micropuncture mineralocorticoid effects demonstrated with sodium present are related to the bosentan effects on net acid excretion (NAE) and acid production reported in salt-restricted rats (11, 12).…”
supporting
confidence: 59%
See 2 more Smart Citations
“…Consistent with this hypothesis, increased proximal tubule proton secretory capacity has been reported in response to metabolic acidosis and was shown to be mediated, at least in part, by increased activation of 18). Micropuncture studies in rat distal tubule have found that net acidification is also stimulated in these segments after a dietary acid load and that the increments are mediated in part by increased bosentan-inhibitable ET activity as modulated both by ET-induced apical Na/H exchange and by 33).While the authors did demonstrate higher plasma aldosterone levels in NaCl-restricted rats with higher acid loads from a high protein diet and that bosentan reduced the hyperaldosteronism, the micropuncture studies, including those showing an effect of sprironolactone, were performed with perfusate containing high concentrations of sodium (10). Since mineralocorticoid excess has no effect on renal or systemic acid-base equilibrium in NaCl-restricted acidotic dogs with high acid loads (9), it is unclear how the micropuncture mineralocorticoid effects demonstrated with sodium present are related to the bosentan effects on net acid excretion (NAE) and acid production reported in salt-restricted rats (11, 12).…”
supporting
confidence: 59%
“…Consistent with this hypothesis, increased proximal tubule proton secretory capacity has been reported in response to metabolic acidosis and was shown to be mediated, at least in part, by increased activation of ET-B (17,18). Micropuncture studies in rat distal tubule have found that net acidification is also stimulated in these segments after a dietary acid load and that the increments are mediated in part by increased bosentan-inhibitable ET activity as modulated both by ET-induced apical Na/H exchange and by ET-induced hyperaldosteronism (12,33).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Possible mechanisms for the deleterious effect of acidosis on GFR may be the inadvertent pro-fibrotic effects of inducing regulatory mechanisms in the kidney, such as increased renal ammonium production, endothelin-A receptor activation and prolonged activation of the renin-angiotensin system. [11][12][13] A systematic review of six randomised controlled trials which administered oral sodium bicarbonate to pre-dialysis CKD patients, versus standard of care treatment or placebo, demonstrated a net improvement in GFR with alkali therapy, as well as reduced initiation of renal replacement and no safety concerns in the longer term. 14 Hence, this appears to be a safe and inexpensive therapy to delay progression of CKD.…”
Section: Sodium Bicarbonatementioning
confidence: 99%
“…Others have suggested that the stimulation of new bicarbonate production in the kidney alkalinizes the interstitium thereby encouraging precipitation of calcium in the kidney and renal injury (6). Finally, studies in rats using the remnant kidney model of CKD indicated that the decline in GFR was mediated in part by the actions of excess aldosterone and endothelin, the latter acting via activation of endothelin A receptors (14,20,22).The studies cited above suggest that metabolic acidosis when present can contribute to progression of CKD, and therefore under these circumstances base treatment is warranted. However, the magnitude of hypobicarbonatemia present in patients with CKD is variable and some patients can actually have a normal serum [HCO 3 Ϫ ] even in the face of severe renal failure (19).…”
mentioning
confidence: 99%